FABRE, Georges; MAYER, Marc; RODÀ, Isabel. Inscriptions Romaines de Catalogne, IV. Barcino. Paris: Diffusion de Boccard, 1997. - Funari, Pedro Paulo A. (Classica - Revista Brasileira de Estudos Clássicos, 1997)
.